Synthesis And Biological Activity Of 2-((3-cyano-4,6-distyrylpyridin-2-yl) Thio) Acetamide And Its Cyclized Form - Negmari, yousef; Shaban A. A, Abdel-raheem; Adel M., Kamal El-dean; Reda, Hassanien; Mohamed E. A., El-sayed .; Aly A., Abd-ella (جامعة الوادي - University of Eloued, 2020)
In this paper, 2-((3-Cyano-4,6-distyrylpyridin-2-yl)thio)acetamide (2) and its cyclized form, 3- amino-4,6-distyrylthieno[2,3-b]pyridine-2-carboxamide (3), were prepared and their structure characterizations were performed by the means of elemental and spectroscopic analyses. Their biological activity as insecticides against cowpea aphid Aphis craccivora Koch using acetamiprid insecticide as a reference was studied. The bioassay results for compounds (2) and (3) against nymphs of cowpea aphid showed that the LC50 values were 0.192 and 0.841 ppm, respectively, after 24 h of treatment but the LC50 values were 0.041 and 0.095 ppm, respectively, after 48 h of treatment. Furthermore, the bioassay results for compounds (2) and (3) showed that the LC50 values were 1.233 and 2.949 ppm, respectively, after 24 h of treatment and the LC50 values were 0.142 and 0.270 ppm, respectively, after 48 h of treatment against adults of cowpea aphid. Given these observations, it has been found that there is a remarkable relationship between the biological activity and the structure of the used compounds.
Keywords: Synthesis; Insecticidal activity; Acetamiprid; Cowpea aphid; Characterization.